1998
DOI: 10.1034/j.1600-0412.1998.770315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen‐progestin hormonal replacement therapy on plasma antithrombin III of postmenopausal women

Abstract: These data suggest that oral conjugated estrogen replacement reduces functional ATIII, whereas transdermal estradiol replacement therapy does not modify it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Antithrombin III (AT III) is a potent coagulation inhibitor that may increase the risk of thrombosis if not present in adequate levels (Bonduki et al 1998). Oral estrogens decrease AT III levels whereas transdermal estrogens appear to have no effect on antithrombin III levels.…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…Antithrombin III (AT III) is a potent coagulation inhibitor that may increase the risk of thrombosis if not present in adequate levels (Bonduki et al 1998). Oral estrogens decrease AT III levels whereas transdermal estrogens appear to have no effect on antithrombin III levels.…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…In spite of the many studies conducted in the field, controversies persist concerning hormone replacement therapy (HRT) effects upon blood coagulation and fibrinolysis. More pronounced effects have been reported for oral than for transdermal supply of oestrogen [12, 16, 20]. Furthermore, study results have differed between studies of unopposed oestrogen [3, 4, 9, 12, 14, 15, 17] and combined oestrogen–progestagens [3, 10, 11, 13–16].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of antithrombin is diminished by oral cHRT and not affected by transdermal cHRT. 14 Other studies indicated an increase of antithrombin concentration by HRT 21,38 or contrarily a decrease, 27 the effects of cHRT being more pronounced than those of oral ERT. Again, other studies have failed to show alterations in activity or concentration of antithrombin.…”
Section: Changes In Anticoagulant Variablesmentioning
confidence: 97%
“…12,13 Oral ERT appears to reduce the level of fibrinogen. 14,15 Trials in which the effects of transdermal ERT were tested did not show an effect on plasma fibrinogen levels. 16,17 cHRT has no consistent effect on plasma fibrinogen levels.…”
Section: Changes In Procoagulant Variablesmentioning
confidence: 99%